Perancangan Sistem Informasi E-Procurement Untuj Media Pembelajaran Pada Prodi Teknologi Rekayasa Logistik Berbasis Web Di Politeknik Jambi. - Helza Triana; Bella Suryani; Raidatus Soleha; Clara Alyusan (Institut Teknologi Adhi Tama Surabaya, 2025)
In the era of globalization and rapid advancements in digital technology, information systems play a pivotal role in enhancing operational efficiency across various sectors, including education and industry. One of the critical applications of information systems lies in warehouse management and procurement processes. This study aims to design and develop a web-based warehouse management and e-procurement information system for the Logistics Engineering Technology Study Program (TRLOG) at Jambi Polytechnic. The proposed system is intended to support practical learning activities, particularly in the Procurement Management course, by providing a realistic simulation of the e-procurement process—ranging from vendor registration, proposal submission, evaluation, to winner selection and purchasing procedures. The research methodology comprises a literature review, requirements analysis, system design, and web-based implementation. The findings indicate that the implementation of this information system significantly improves the effectiveness and efficiency of practical learning, facilitates logistics data management, and enhances students’ comprehension and preparedness for real-world industrial practices. Accordingly, the developed e-procurement and warehouse management system is expected to serve as an innovative and technology-driven solution for supporting vocational education.